2000
DOI: 10.1097/00005373-200008000-00013
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Head Injury Using T2*-Weighted Gradient-Echo Imaging

Abstract: T2*-GE was found to be useful for evaluating the clinical symptoms of head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 12 publications
1
46
1
2
Order By: Relevance
“…There are currently conflicting results on the relationship between outcome and the number of lesions on MRI, given the few comparison studies available. Some studies report that lesions on T2WI (Chastain et al, 2009;Gerber et al, 2004;Sigmund et al, 2007), FLAIR (Chastain et al, 2009;Sigmund et al, 2007), T2*-GRE (Gerber et al, 2004;Yanagawa et al, 2000), and SWI (Sigmund et al, 2007;Tong et al, 2004), can discriminate or correlate with outcomes. Other studies report that there is no correlation between outcomes and lesions on T2WI (Yanagawa et al, 2000), T2*-GRE (Scheid et al, 2003), and SWI (Chastain et al, 2009).…”
Section: Mrimentioning
confidence: 99%
“…There are currently conflicting results on the relationship between outcome and the number of lesions on MRI, given the few comparison studies available. Some studies report that lesions on T2WI (Chastain et al, 2009;Gerber et al, 2004;Sigmund et al, 2007), FLAIR (Chastain et al, 2009;Sigmund et al, 2007), T2*-GRE (Gerber et al, 2004;Yanagawa et al, 2000), and SWI (Sigmund et al, 2007;Tong et al, 2004), can discriminate or correlate with outcomes. Other studies report that there is no correlation between outcomes and lesions on T2WI (Yanagawa et al, 2000), T2*-GRE (Scheid et al, 2003), and SWI (Chastain et al, 2009).…”
Section: Mrimentioning
confidence: 99%
“…4) The number of hemorrhages due to head injury was minimized by excluding patients with a past history of moderate and severe head injury because T 2 *-weighted MR imaging shows minute hemorrhages in patients with severe head trauma. 29) The present study showed that hypertensive patients with symptomatic hemorrhage tended to have asymptomatic minute hemorrhages, compared with patients with symptomatic cerebral infarction. Hypointense lesions in the globus pallidus were not counted, because globus pallidus in the elderly tends to contain calcification.…”
Section: Discussionmentioning
confidence: 47%
“…The ecoplanar gradient sequence at the T2* weighing contributed to demonstrate chronic and acute intra-axial hemorrhage 32 . The utility of FLAIR images in diagnosing swelling and subarachnoid hemorrhage was studied by many researchers 28,29,33 .…”
Section: Discussionmentioning
confidence: 99%